Religious vocation as a latent identity for school principals - Clancy, Patrick (Economic & Social Studies, 1983)
Abstract: This paper is concerned with studying schools as organisations. The effects of religious vocation as a latent identity of school principals is central to the analysis. Some of the organisational processes of schools which are run by religious congregations are examined. In particular the implications for staff authority relations and for boundary exchanges with clients are explored. The substantive discussion serves to demonstrate the analytical scope of the latent identity concept. Some suggestions are made for refining the concept to improve its analytic potential.
Keywords: Education; Religious Organisations